New Perspectives for Postmortem Human Satellite Cells of Different Embryological Origin - Pietrangelo, Tiziana; Demontis, Roberto; Santangelo, Carmen; Pini, Niccolò; Bonelli, Martina; Rosato, Enrica; Roberti, Paola; Locatelli, Marcello; Tartaglia, Angela; Marramiero, Lorenzo; Verratti, Vittore; Bondi, Danilo; et al. (Frontiers in Physiology, 2022)
Human postmortem skeletal muscles are a unique source of satellite cells for skeletal muscle regenerative studies. Presomite and somite satellite cells obtained by postmortem muscles have been established as populations of human skeletal muscle precursor cells able to proliferate and differentiate in vitro. It is extremely interesting to have access to large amount of postmortem human skeletal muscle precursor cells, especially from craniofacial as well as limb skeletal muscles in order to evaluate their potential application not only for fundamental understanding of muscle physiology and diseases, but also for drug testing in a challenging 3D shaping muscles like for skeletal muscle microphysiological systems